The Role of Islamic Finance in Achieving Sustainable Development in Indonesia: Peran Keuangan Syariah dalam Mewujudkan Pembangunan Berkelanjutan di Indonesia - Paisal Rahmat; Ira Nabila Nasution; Fitri Amanda Nasution; Lely Apriani (Al Dzahab, 2025)
Purpose: This study aims to determine the role of Islamic finance in achieving sustainable development in Indonesia and what roles Islamic finance plays in achieving sustainable development. Design/methodology/approach: This research method uses a qualitative approach with library research techniques to explore and analyze literature relevant to the topic of the role of Islamic finance in achieving sustainable development. The qualitative approach was chosen because it allows researchers to understand the phenomenon in depth, including related social, economic, and environmental aspects. Findings: The results of this study indicate that Zakat, green sukuk, and Sharia microfinance play a very important role in achieving sustainability goals. They also have great potential to contribute to the achievement of sustainable development goals through the introduction of a green economy and environmentally friendly practices. Research  implications: The results of this study show that there is great potential to contribute to the achievement of sustainable development goals in Indonesia through zakat, green sukuk, and microeconomic financing.